IMPLEMENTASI TECHNOLOGY ACCEPTANCE MODEL (TAM) DALAM ONLINE SHOPPING - LOEKAMTO, ANDRY (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Technology Acceptance Model or commonly called the Technology Acceptance Model (TAM) is used to predict user acceptance of new technologies. As technology has developed rapidly, the Internet world also experienced the development and application of TAM in internet business start walking Online shopping or online shop via the internet is the process of purchasing goods or services from those who sell over the internet. Applications implementation of TAM in Online Shopping is influenced by the experience of using the Internet will impact the ease and provide benefits to users, which directly affects the willingness of Internet users to buy goods from online stores.